A study on the Writing Mistakes Made by Persian language Arab Learners - جوني, رنا (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This research studies the grammatical mistakes made by Arabic-speaking learners writing in Persian language. The study detects the reasons behind these mistakes so that the teachers are made aware of them during the teaching process. It also helps take them into consideration in the process of syllabus design. The study uses the descriptive analytical method. The research sample is a number of university students learning Persian language at the Iranian Culture Center in the city of Lattakia. The chosen sample is particularly important because it represents highly motivated learners who are not obliged to learn Persian since it is not part of their academic curriculum. The material subject to analysis is the final written exams given by learners of beginner, intermediate, and advanced proficiency levels. The importance of selecting written exams as research material springs from the fact that they genuinely display the learners' linguistic efforts. They can also help determine the learners' weaknesses by narrowing down their mistakes to the most frequently made and the reasons behind them. The framework of the study is divided into: a theoretical section, which provides a definition of mistake analysis، its stages، and its practical objective; an empirical section, which consists of an applied study which includes determining the sample, collecting it, and sorting out the different kinds of the learners' mistakes and their frequency by resorting to statistical processes. The study has shown different kinds of mistakes in the learners' writing, grammatical, morphological, and semantic. It clearly shows that spelling mistakes are the most frequent ones in the Arab learners' writing، which can be attributed to language interference (also known as L1 interference), which "in reality means drawing the learner's linguistic experience from the mother tongue to the language being learned."